Key Factors for Digital Marketing Adoption in the Tourism Industry: Case Study of the Mandalika Special Economic Zone - Dede Suleman; Puji Yuniarti; Raden Ati Haryati; Dede Mustomi; Joko Ariawan; Wiwin Wianti (Dinasti International Journal of Digital Business Management, 2024)
The tourism industry is a very dynamic and competitive sector, where the adoption of digital technology is the key to increasing competitiveness and operational efficiency. The Mandalika Special Economic Zone (KEK), as one of the leading tourism destinations in Indonesia, faces challenges and opportunities in adopting digital marketing to attract tourists and investment. This research aims to identify key factors that influence digital marketing adoption in the Mandalika SEZ using a technology–organization–environment (TOE) framework. Based on data collected from 310 respondents through an online survey, the research results show that compatibility, entrepreneurship, competitive pressure, changes in the digital environment, and shortage of human resources have a significant influence on digital marketing adoption. Compatibility was found to be the most significant factor influencing digital marketing adoption, while relative advantage and complexity had no significant influence. These results provide practical and theoretical insights for stakeholders in the tourism industry to implement effective and efficient digital marketing strategies. In this way, the Mandalika SEZ can maximize its potential as a world-class tourism destination and contribute to regional and national economic growth.